‘Will my fingerprint be enough?’: secondary school students struggle to purchase a healthy, tasty and sustainable meal on the UK free school meal allowance - Sundus Mahdi; Annie Connolly; Bob Doherty; Maria Bryant (Public Health Nutrition)
Abstract